Incidental Intracranial Aneurysm in a Dog Detected by 16-Multidetector Row Computed Tomography Angiography. (7th February 2013) - Bertolini, Giovanna
Abstract : This paper describes a small intracranial aneurysm incidentally found in a 24-month-old Nova Scotia Duck Tolling Retriever evaluated for a recent history of lethargy, fever, and cervical pain. The clinicopathological analysis revealed leukocytosis, and increased haptoglobin and C-reactive protein consistent with severe flogistic process. Nonenhanced computed tomography of the brain and cervical spine showed a diffuse encephalopathy and moderate cervical syringohydromyelia. Computed tomography angiography series of the brain showed a small saccular dilation at the joining point of the two rostral cerebral arteries consistent with a small aneurysm. Cerebrospinal fluid examination led to the final diagnosis of aseptic meningitis. The dog was discharge with a long-term corticosteroid therapy for the meningitis. At two-month follow-up evaluation, the cerebrospinal fluid examination was normal and the computed tomography of the brain showed no abnormalities except for the stable aneurysm. To our knowledge, this is the first description of a spontaneous cerebral aneurysm in dogs and serves to broaden the spectrum of cerebrovascular diseases in this species.